The Phenomenon of Brand Tribalism in Online Games Business - Lasmy, Lasmy; Mehan, Charu (International Research Journal of Business Studies, 2024)
This research aims to analyze the influence of telepresence and community factors on brand tribalism and the interest in purchasing virtual items in the online games, especially MMORPG Final Fantasy XIV in Indonesia. The empirical research was a quantitative method and data were collected from 110 respondents through online surveys in the game's Facebook and discord groups, who is the players of online game, MMORPG Final Fantasy XIV in Indonesia. The research model was tested using statistical software, SPSS. Results indicate that telepresence and community factors significantly impact brand tribalism and interest in purchasing virtual items. However, no significant relationship was found between brand tribalism and interest in virtual item purchase. This research fills the gap in previous research, regarding customer behavior in online games and the variables studied such as brand tribalism, telepresence and community factors. Similar research is rarely discussed in previous research.